Relationship Between Ginsenoside Rg3 and Metabolic Syndrome - Lee, Hyunji; Kong, Gyeyeong; Tran, Quangdon; Kim, Chaeyeong; Park, Jisoo; Park, Jongsun (Frontiers in Pharmacology, 2020)
Metabolic syndrome is an important public health issue and is associated with a more affluent lifestyle. Many studies of metabolic syndrome have been reported, but its pathogenesis remains unclear and there is no effective treatment. The ability of natural compounds to ameliorate metabolic syndrome is currently under investigation. Unlike synthetic chemicals, such natural products have proven utility in various fields. For example, ginseng is used in dietary supplements and cosmetics. In this review, we describe the potential of ginsenoside Rg3, a component of ginseng, in the treatment of the metabolic syndrome.